EFEKTIVITAS DAN DAMPAK PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT MANDIRI PERDESAAN (PNPM-MPd) TERHADAP PENINGKATAN KESEJAHTERAAN DAN KESEMPATAN KERJA RUMAH TANGGA SASARAN DI KECAMATAN ABIANSEMAL KABUPATEN BADUNG - Putra, I Gusti Putu; Sri Budhi, Made Kembar (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 04.NO.03.TAHUN 2015, 2015)
Handling the problem of poverty is one of the issues of concern to the government in any country. Various strategies have been implemented by the government to improve the lives of people still do not show satisfactory results shown with still many poor people. Similarly, the problem of poverty in the district  Abiansemal  one of the efforts taken in poverty reduction is based on community empowerment through PNPM .                The purpose of this study was to assess the effectiveness and impact of PNPM program to Welfare and Employment Opportunities Target Households in the district  Abiansemal. The analytical tool used in the study is to determine the level of statistical deskiptif  program effectiveness, and two different test average pairwise observations to determine the impact of the program on Welfare and Employment Opportunities Target Households. Results of the analysis showed that the effectiveness of PNPM in the district  Abiansemal as very effective at 84.52 persen. Based on two different test average pairwise observations income and employment opportunities Target Households showed significant results in alpha 5 percent. The average income of the month before the program Rp.2.066.000, after  the program Rp.2.961.000 , - and the number of working hours on average, one day before the program 5.86 hours,  increased to 8.29 hours after the program. It is recommended that the PNPM continuously improved and developed with the open jobs or employment opportunities available to work so as
Keywords: effectiveness , welfare , employment